Cryptocurrency Based Money Laundering in Indonesia - Sitompul, Ariman (International Asia Of Law and Money Laundering (IAML), 2025)
Money laundering with Cryptocurrency in Indonesia in the use of digital currencies provides a loophole for criminals to hide the results of criminal acts through money laundering practices. This article reviews various strategies used in money laundering using crypto assets, with the aim of providing a deeper understanding of this issue. This research applies the normative study method by analyzing legal aspects based on literature as well as the latest developments related to money laundering and cryptocurrencies. Money laundering through crypto assets is carried out in order to disguise the source of illegal funds. Some of the commonly used methods include transactions over the dark network as well as the use of unlicensed mixing services. This crime has been regulated in various laws and regulations that aim to prevent and eradicate the practice of money laundering through cryptocurrencies.